Pengaruh Citra Merek, Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian Konsumen Indomaret Melalui Keunggulan Bersaing Sebagai Variabel Intervening: The Influence of Brand Image, Service Quality and Price On Indomaret Consumer Purchasing Decisions Through Competitive Advantage As An Intervening Variable - Dwi Rizki Aldiesi; Nanang Wahyudin (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Modern retail competition is getting tougher, making Indomaret need to pay attention to brand image, service quality and superior prices in order to attract purchasing decisions. The aim of this research is to analyze the effect of brand image, service quality and price on Indomaret consumers' purchasing decisions with competitive advantage as intervening variables. This research uses a descriptive quantitative approach. Data collection was carried out by distributing questionnaires by Accidental Sampling to 161 respondents. Data analysis used Structural Equation Modeling (SEM) with SmartPLS software. The results of this study show that partially brand image, service quality, and price have a positive and significant effect on competitive advantage. Partially brand image, service quality, price and competitive advantage have a positive and significant effect on purchasing decisions. The mediation test results show that brand image has a positive and significant effect on purchasing decisions mediated by competitive advantage. Service quality has a positive and significant effect on purchasing decisions mediated by competitive advantage. Price has a positive and significant effect on purchasing decisions mediated by competitive advantage. Keywords: brand image, competitive advantage, purchase decision, service quality